2015
DOI: 10.1177/0218492315576282
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve repair for rheumatic mitral regurgitation: Mid-term results

Abstract: Mitral valve repair for rheumatic mitral regurgitation is associated with a significant rate of valve failure and reoperation. However, it has a satisfactory survival rate and is a good alternative to valve replacement, especially for young patients, to avoid the life-long risks of a prosthetic valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…These authors extracted data from seven selected studies, performed a pooled analysis and showed that the MV repair group has lower 30-day mortality, higher long-term survival, fewer postoperative major adverse events than the MV replacement group, while displaying an acceptable reoperation rate. Another study (11) suggested MV repair is a better alternative to valve replacement for RHD patients, corroborating the findings in the current meta-analysis. Pooled analysis showed that freedom from adverse events in patients after rheumatic MV repair surgery was 97.5% (95% CI, 95.2-99.8%).…”
Section: Discussionsupporting
confidence: 90%
“…These authors extracted data from seven selected studies, performed a pooled analysis and showed that the MV repair group has lower 30-day mortality, higher long-term survival, fewer postoperative major adverse events than the MV replacement group, while displaying an acceptable reoperation rate. Another study (11) suggested MV repair is a better alternative to valve replacement for RHD patients, corroborating the findings in the current meta-analysis. Pooled analysis showed that freedom from adverse events in patients after rheumatic MV repair surgery was 97.5% (95% CI, 95.2-99.8%).…”
Section: Discussionsupporting
confidence: 90%
“…With two thirds of mitral patients over the age of forty showing degrees of leaflet thickening and rigidity [113], the repairable group is limited to a minority of the patients and even with sophisticated surgical techniques have high re-operation rates [114]. As such, prosthetic solutions need to resolve the dilemma of early degeneration in bioprosthetic valves [115] versus high thrombo-embolic complications [116] in mechanical valves for whom adherence is more challenging [117].…”
Section: Current Epidemiology Of Gas Arf and Rhd Around The Worldmentioning
confidence: 99%
“…Dillon et al [70] reported 83.3 AE 4.3% 10-year survival and 98.4 AE 0.9% freedom from reoperation. Waikittipong [71] reports a very high rate of success for complex valve repair using primarily leaflet mobilization with chordal cutting, papillary muscle splitting, and commissurotomy for type IIIb restricted leaflet motion and neochords, chordal transfer, or shortening for type II leaflet prolapse. The author emphasizes three criteria for successful repair: selection of patients who are beyond the acute inflammatory phase with suitable morphology for repair; repair based on surgical principles of leaflet mobilization, correction of prolapse and ring annuloplasty; and secondary prophylaxis using penicillin.…”
Section: Interventional and Surgical Management Of Rheumatic Heart DImentioning
confidence: 99%